New Hadamard’s Inequality for (α1, m1)-(α2, m2)-Preinvex Functions on the Co-Ordinates: khaled boukerrioua, B. Meftah, T. Chiheb - Team, Support (Thai Journal of Mathematics, 2018)
In this paper, we introduce some new classes of convex functions called (α, m)-preinvex, (α1, m1)-(α2, m2)-preinvex functions on the co-ordinates, and then we derive some new Hermite-Hadamard type inequalities whose modulus of their mixed derivatives lies in these novel classes of functions.